Unravelling nutrient dynamics and mixed layer depth variability in the equatorial Atlantic: insights from 10°W meridional section monitoring - Kouame, Kanga Désiré; N’Guessan, Kouadio Benjamin; Kouassi, Aka Marcel; Trokourey, Albert; Ostrowski, Marek; Brehmer, Patrice (Frontiers in Marine Science, 2024)
The ocean, a pivotal component of the Earth’s climate system, exerts a profound global influence through intricate physical and biological interactions within its surface layer. This interplay centers around the mixed layer (ML), integral for energy exchange driven by oceanic currents. An essential regulatory function of the ocean involves orchestrating the distribution of chemical elements, with nitrate assuming a pivotal role in oceanic primary production. Nutrient availability, a cornerstone of primary production, hinges on the mixed layer depth (MLD) dynamics, modulated by many mechanisms, including upwelling and convection. This study unravels the interplay between nutrient variability and MLD depth, focusing on the Gulf of Guinea (GG) region in the equatorial Atlantic. Characterization of the study area reveals distinctive sea surface temperature (SST), salinity (SSS), and current patterns. The South Equatorial Undercurrent (SEUC) and Equatorial Undercurrent (EUC) play vital roles in surface nutrient transport. Nitrate distribution unveils latitudinal variations, exhibiting pronounced enrichment during boreal summer and winter. The equatorial region experiences a strengthening of MLDs from 10.5 to 35.33 m in summer, which increases the nitrate input from 0 to 2.06 mmol m-3 in the surface layers in the mixed layer. In contrast, boreal winters experience more intense MLDs that vary between 20.5 and 64.50 m, supporting high nitrate concentrations of 2.96 to 7.49 mmol m-3, challenging previous hypotheses. This equatorial enrichment is supported by low nitracline ranging from 5.47 to 46.19 m. Beyond the equator, the subequatorial and subtropical regions, despite the observed deepening of the ML, present low nitrate concentrations (less than 0.5 mmol m-3) with a nitracline that does not reach the ML. However, at 6°S and 9°S, a respective increase in nitrate content of 0.66 mmol m-3 and 1.2 mmol m-3 influenced by internal waves, advection and surface currents is observed. Temperature, salinity, and atmospheric fluxes shape nutrient distribution and primary production dynamics. These findings illuminate the intricate relationships between oceanographic processes, nutrient availability, and marine ecosystem productivity. A holistic understanding is crucial for sustainable resource management and fisheries in the equatorial Atlantic and beyond.